2022
DOI: 10.1002/1878-0261.13227
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the DNA damage response and repair in cancer through nucleotide metabolism

Abstract: The exploitation of the DNA damage response and DNA repair proficiency of cancer cells is an important anticancer strategy. The replication and repair of DNA are dependent upon the supply of deoxynucleoside triphosphate (dNTP) building blocks, which are produced and maintained by nucleotide metabolic pathways. Enzymes within these pathways can be promising targets to selectively induce toxic DNA lesions in cancer cells. These same pathways also activate antimetabolites, an important group of chemotherapies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 215 publications
(270 reference statements)
0
13
0
Order By: Relevance
“…SAMHD1 has multifaceted roles important to human health and disease, through its enzymatic activity as a central dNTPase and through its non-catalytic activities 2 . More recently, we and others have reported that SAMHD1 can also deactivate antileukemic drugs, notably cytarabine, the backbone therapy for AML, and thereby limit anticancer efficacy 39,40,50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAMHD1 has multifaceted roles important to human health and disease, through its enzymatic activity as a central dNTPase and through its non-catalytic activities 2 . More recently, we and others have reported that SAMHD1 can also deactivate antileukemic drugs, notably cytarabine, the backbone therapy for AML, and thereby limit anticancer efficacy 39,40,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Sterile alpha motif and histidine-aspartic acid domain containing protein-1 (SAMHD1) is a deoxynucleoside triphosphate (dNTP) triphosphohydrolase with critical roles in human health and disease 1,2 . Belonging to the HD-domain superfamily, a group of metal-dependent phosphohydrolases 3 , SAMHD1 catalyses the hydrolysis of canonical dNTPs producing the cognate deoxynucleoside and inorganic triphosphate 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Mutations induced by GI were increased within the TME compared to cells under standard culture conditions, and hypoxic conditions also contributed to mutagenesis ( Bindra and Glazer, 2005 ), suggesting the TME can be an indispensable inducer of GI in cancer cells ( Chan et al, 2009 ; Bizzarri and Cucina, 2014 ; Sonugur and Akbulut, 2019 ). It was convinced that hypoxia is a major factor leading to GI, and increased reactive oxygen species can induce single- and double-strand DNA breaks which promote the translocations, deletions, and amplifications in tumor cells ( Degtyareva et al, 2013 ; Helleday and Rudd, 2022 ). This might indicate the possibility of GI-based signature having implications in reflecting the TME and determining treatment, while current evidence is relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…One-carbon (1C) metabolism is central to the supply of nucleotides for DNA synthesis and repair. Without sufficient nucleotide supply to meet the proliferative demands, cells undergo cell cycle arrest or cell death due to replication stress and genomic instability [1][2][3] . Enzymes involved in the 1C metabolism pathway are commonly upregulated in cancer to produce nucleotides and amino acids required for rapid proliferation [4][5][6] .…”
mentioning
confidence: 99%